Prática dialógica de leitura: leitura profunda, possibilidades e desafios - Fraga, Amanda Cavalaro (2023)
This research is inserted in the area of Applied Linguistics and aims to investigate the Group Thinking Aloud (“Pensar Alto em Grupo” - ZANOTTO, 1992; 1995; 2014ab) as a dialogical practice of literacy, aiming at the formation of readers who construct meaning and the formation of the teacher-researcher as a literacy agent. Group Thinking Aloud is a dialogic and collaborative reading practice, anchored in the epistemology of dialogism (BAKHTIN, 2011) and dialogicity (FREIRE, 2020ab) and its principle is to guarantee multiple readings, legitimizing the different voices within a reflective and dialogic environment, seeking the collective construction of meanings. The research is justified by the need for reflection in relation to autonomous literacy practices (STREET, 2014), which objectivist and monological application underlies school practices, which results in the merely metalinguistic conception of reading in the classroom, as well as by the need to seek new theoretical-methodological conceptions that can contribute to paradigmatic changes in favor of reading practices that promote Deep Reading (WOLF, 2019), with the emergence of responsivereflective thinking from readers. This is a qualitative research, inserted in the interpretativist paradigm: a research-action carried out with teenagers (aged between 15 and 18 years) attending 1st and 2nd grades of high school, in a private school in the south zone of São Paulo - group in which I played the role of teacher-mediator in four experiences. For data analysis and discussion, I based myself on the following guiding questions: a) Can the dialogical practice of reading, Think Aloud in Groups, contribute to my training as a researcher and literacy agent? b) Does the Think Aloud in Groups enable changes in the students' reality in relation to their reading practices of the literary text, making them protagonists in the construction of meaning? c) What are the challenges and possibilities for the teacher-literacy agent when using the dialogical practice of reading, Think Aloud in Groups? The data revealed that the dialogical reading practice researched provided a break from the monological paradigm in my performance, promoting the reflexive action of the students. The experiences made possible changes in the students' perspectives, allowing a real construction of meaning on the part of the students, making them protagonists - critical and reflective - about the act of reading. Furthermore, I could attest to the multiple challenges and possibilities of the literacy agent teacher. Although some difficulties were noticeable, I can attest to the potential of the practice to generate possibilities of positive change